ANALISIS PENYEBAB KURANGNYA MOTIVASI BELAJAR IPS SISWA KELAS V SDN 01 SEMANGET - Sukristin Sukristin (JURNAL PENDIDIKAN DASAR, 2022)
Abstract: this research aims to find out the cause of motivation lack in social science learning in Public Elementary School 01 Semanget, sub-district Entikong. The method is qualitative-descriptive. The results of this research are 1) based on the questionnaire result shows that the good criteria is in 10%, the good enough criteria is in 20% and the inadequate criteria is in 70%. It shows the highest questionnaire result percentage is in the inadequate criteria. 2) and the result of interview shows that the causes of motivation lack in science learning are the student competence, the student environment condition, and the technology development in this era. 3) according to the documentation data shows that the student score from the theme 1 to the theme 3, including the criteria of science learning score is in “the inadequate criteria”. It can conclude that the student motivation is inadequacy and the causes of student motivation lack in social science learning are 1) the student competence, 2) the environment condition, and 3) the effect of technology developmentKeyword : learning outcomes, motivation, technologicaldevelopment Abstrak: Penelitian ini bertujuan untuk mengetahuai penyebab kurangnya motivasi belajar IPS di SDN 01 Semanget Kecamatan Entikong.  Metode penelitian ini adalah Kwalitataf dengan pendekatan deskriptif kwalititatif. Hasil penelitian 1) dilihat dari hasil angket menunjukan kriteria baik  berada pada 10%, kriteria cukup  20% dan kriteria kurang berada pada 70%. Presentase hasil angket yang lebih banyak adalah kriteria kurang,  2) hasil wawancara, penyebab kurangnya motivasi belajar IPS adalah karena disebabkan oleh kemampuan siswa itu sendiri, kondisi lingkungan siswa, dan perkembangan teknologi pada saat ini,  3) dari data dokumentasi menunjukan  nilai siswa dari tema 1 sampai tema 3, berserta kriteria nilai IPS siswa adalah masih kurang. Penelitian ini dapat disimpulkan bahwa motivasi siswa masih sangat kurang, dan penyebab dari kurangnya motivasi belajar IPS siswa kelas V, ada tiga penyebab yaitu: 1) Kemampuan Siswa, 2) Kondidsi lingkungan, 3) Pengaruh Perkembnagan teknologi.Kata Kunci : Hasil Belajar, motivasi, perkembangan teknlogi